Identification of Fusarium verticillioides Resistance Alleles in Three Maize Populations With Teosinte Gene Introgression - Feng, Xuanjun; Xiong, Hao; Zheng, Dan; Xin, Xiaobing; Zhang, Xuemei; Wang, Qingjun; Wu, Fengkai; Xu, Jie; Lu, Yanli (Frontiers in Plant Science, 2022)
Fusarium ear rot (FER) is a common fungal disease in maize (Zea mays L.) caused by Fusarium verticillioides. Resistant germplasm resources for FER are rare in cultivated maize; however, teosintes (Z. mays ssp. parviglumis and Z. mays ssp. diploperennis), which are wild related species of maize, have the potential to offer a novel source of resistance alleles to enhance pathogen resistance in modern maize. The aim of this study was therefore to identify favorable alleles that confer significant levels of resistance towards FER. Three populations of BC2F8 recombinant inbred lines (RILs) were developed by crossing two different teosintes, Z. diploperennis and Z. parviglumis, with maize inbred lines B73 and Zheng58, and were screened for FER resistance. We found that Z. diploperennis and Z. parviglumis had higher resistance towards F. verticillioides in the leaves than B73 and Zheng58 did. However, the resistance towards F. verticillioides in the leaf and ear was unrelated among RILs. FER resistance was positively correlated with grain yield in the B73 × diploperennis (BD) and Zheng58 × parviglumis (ZP) populations, partly because the quantitative trait loci (QTLs) of FER resistance and yield traits were located close together. Four coincident QTLs (qFERbd5.177, qFERbd10.140, qFERzp4.066, and qFERzp5.116) and two highly reliable resistance–yield synergistic QTLs (qFERbd10.140 and qFERzp4.066) were identified in the BD and ZP populations, opening up the possibility of breeding for FER resistance without reducing yield.